Tinjauan yuridis penerapan asas tinjauan yuridis penerapan asas cepat sederhana dan biaya ringan bagi hakim dalam memutus sengketa tata usaha negaran di pengadilan tata usaha negara pekanbaru: Application of Simple Fast Asasa Low Cost for Judges in deciding Disputes, Pekanbaru State Administrative Court - Susi Atdriani; Saut Maruli Tua Manik (JURNAL RISET INDRAGIRI, 2023)
Indonesia is a state of law, so the existence of the judiciary is very important because it functions as the last bastion of law enforcement within the country. Therefore, in the constitution of the state of Indonesia as stated in the 1945 Constitution of the Republic of Indonesia in Article 24 paragraph (2) it is stated that judicial power is exercised by a Supreme Court and judicial bodies under it within the General Court environment, the Religious Court environment, the Military Court, State Administrative Court environment, and by a Constitutional Court. State Administrative Court (hereinafter referred to as Administrative Court) is a court within the scope of public law, which has the duty and authority to "examine, decide and resolve state administration disputes, namely a dispute that arises in the field of state administration law between persons or civil legal entities (community members) with TUN Bodies or Officials (government) both at the central and regional levels. As a result of the issuance of a TUN Decree (beschikking), including employment disputes based on applicable laws and regulations" (Article 50 Jo. Article 1 point 4 of the Administrative Court Law). This study aims to find out the juridical analysis of the application of the simple fast principle and low cost for judges in deciding state administrative disputes at the Pekanbaru state administrative court that has been implemented, to find out the obstacles found in the application of the simple fast principle and low cost as well as how judges try to Realizing the Principle of Fast, Simple and Low Cost for Judges at the Pekanbaru State Administrative Court. The type of research used is normative legal research method. The results of this study indicate that in general the application of the principle of simple fast and low cost has not been implemented optimally based on the State Administrative Court Procedure Law. There are still cases that have been resolved for more than 5 (five) months due to SEMA No. 2 of 2014 is a rule that was just promulgated on March 13, 2014. Therefore, in its implementation, the Pekanbaru State Administrative Court did not immediately run effectively. Because the rule of law generally requires adjustments for some time in order to run effectively. This can be seen from the percentage of cases that were resolved for more than 5 months by judges in 24 cases from 2021 to 2022.